2002
DOI: 10.2172/820722
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Chord Length Sampling for Transport Through a Binary Stochastic Mixture

Abstract: Neutron transport through a special case stochastic mixture is examined, in which spheres of constant radius are uniformly mixed in a matrix material. A Monte Carlo algorithm previously proposed and examined in 2-D has been implemented in a test version of MCNP. The Limited Chord Length Sampling (LCLS) technique provides a means for modeling a binary stochastic mixture as a cell in MCNP. When inside a matrix cell, LCLS uses chord-length sampling to sample the distance to the next stochastic sphere. After a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Donovan and Danon did not examine for their specific problem the approach of using Algorithm B for both materials in the problem. Donovan and Danon extended the LCLS algorithm to the simulation of particle transport through a binary stochastic mixture of spheres of constant radius mixed in a three-dimensional matrix material [9] as well as to the simulation of a single spherical pebble fuel cell [10]. A recent paper by Ji and Martin [11] examined Monte Carlo chord length sampling algorithms for the neutronics analysis of Very High Temperature Gas-Cooled Reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Donovan and Danon did not examine for their specific problem the approach of using Algorithm B for both materials in the problem. Donovan and Danon extended the LCLS algorithm to the simulation of particle transport through a binary stochastic mixture of spheres of constant radius mixed in a three-dimensional matrix material [9] as well as to the simulation of a single spherical pebble fuel cell [10]. A recent paper by Ji and Martin [11] examined Monte Carlo chord length sampling algorithms for the neutronics analysis of Very High Temperature Gas-Cooled Reactors.…”
Section: Introductionmentioning
confidence: 99%
“…As Torquato and Lu [1993] showed, this formula is only an approximation, albeit one that works remarkably well. Several authors [Levitz 1993;Donovan et al 2003;Olson et al 2006] have shown that this formula is incorrect for very small distances (< 1 grain radius), but this is usually ignored in favor of the simple analytical model. We also found the same effect in our experiments (see Figure 6, top), but did not find that accounting for this difference by using tabulations or non-exponential analytical models provided a substantial benefit.…”
Section: The Teleportation Transport Modelmentioning
confidence: 99%